The influence of open space on sub-sale house pricing in Selangor - Manzahari, Mohd Nasrul Hanis; Asmawi, M. Zainora; Abdullah, Alias (IIUM Press, International Islamic University Malaysia, 2017)
The significant expansion of housing industry in Malaysia has attracted the concern of various parties. There are increasing awareness and particular concern about the issue of green areas and open spaces as urban residents start to acknowledge the importance of urban green spaces. The research problem addresses the issue of the importance of open space being ignored due to high prices of real estate. This research aims to study the influence of open space towards house pricing in urban areas. This research also highlights discussions on past studies which provide important lessons and ideas for the research design. Three methods of data collection had been employed which are: (i) literature review; (ii) questionnaire survey; and (iii) site observations. The selected study areas were Taman Melawati, Shah Alam, Subang Jaya and Bandar Baru Bangi. The response rate was 100% with a total respondent of 200. The reliability test was conducted and the results of Cronbach’s alpha value for green areas and its independent variables was 0.895 thus considered acceptable and allowed the research to retain all variables for the analysis. This research found that the consideration of open space in increasing house prices has positive influence towards the determination of housing prices (rs = .091). However, the relationship is weaker compared to other macro and micro factors. The most desirable element of open space is cleanliness (RI = 0.894) while the least desirable element is hierarchy of open space (RI = 0.783), showing that users prefer elements which they can physically observe. Theoretically, the findings of this research are in line with the theories suggested by other literature. The result, as perceived by the respondents, reflects preference for physical and economic factors compared to environmental factor. Based on the findings, the researcher recommends key parties in housing industry to consider open space as an essential factor in determining house prices as well as providing regular maintenance and premium facilities for open spaces within residential areas. As a conclusion, this research has met its outlined objectives and proves that there is a weak positive relationship between open space and house pricing.